PERAN KANTOR URUSAN AGAMA DALAM MENGANTISIPASI PERKAWINAN DI BAWAH TANGAN DI KECAMATAN DUA BOCCOE KABUPATEN BONE - Shintika Rindiyani Guntur; Zulfahmi Alwi; Musyfikah Ilyas (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem in this study is how the role of the Office of Religious Affairs in anticipating underhand marriages in Dua Boccoe District Bone Regency. The type of researchused in this thesis is field research. The results of this study indicatet hattheroleof KUA is very important toanticipatet heoccurrence of under handed marriages. By conducting socialization, counselingand seminars on marriage so as to reducethe number of couples who carry outunder hand marriages, its how sthatthe KUA has carried out its rolewell. The implication of this research is that thereis great hope for KUA to continue implementing steps that anticipatet heoccurrence of under handed marriages in Dua Boccoe District, Bone Regency.